EFFECT OF CYCLOART-24-EN-3-OL FROM EUPHORBIA ROYLEANA LATEX ON NEURO-ENZYME AChE AND OXIDATIVE METABOLISM OF FRESHWATER FISH, CHANNA PUNCTATUS - Tiwari, S.; Pandey, R. P.; Singh, Ajay (African Journal of Traditional, Complementary and Alternative Medicines, 2008)
Cycloart-24-en-3-ol isolated from Euphorbia royleana latex possesses potent piscicidal activity against freshwater predatory fish Channa punctatus. Their short as well as long-term exposure causes significant (P<0.05) time and dose-dependent reversible alteration in the oxidative metabolism of the fish Channa punctatus Cycloart-24-en-3β-ol also shifts fish respiratory pathway, inhibits energy production and AChE activity reversibly may be advantageous for their use as environmentally safe piscicide for controlling the predatory fish C. punctatus population from carp culture ponds.